( х-у)(х+у)-(а-х+у)(а-х-у)-а(2х-а)=0

0 голосов
134 просмотров

( х-у)(х+у)-(а-х+у)(а-х-у)-а(2х-а)=0


Алгебра (12 баллов) | 134 просмотров
Дано ответов: 2
0 голосов

( х-у)(х+у)-(а-х+у)(а-х-у)-а(2х-а)=0

x^2-y^2-(a^2-ax-ay-ax+x^2+xy+ay-xy-y^2)-2ax+a^2=0

 x^2-y^2-a^2+ax+ay+ax-x^2-xy-ay+xy+y^2-2ax+a^2=0  

0=0   

(13.8k баллов)
0 голосов

(x-y)(x+y)-(a-x+y)(a-x-y)-a(2x-a)= \\ \\ =x^2-y^2-a^2+ax+ay+ax-x^2-xy-ay+xy+y^2- \\ \\ -2ax+a^2=0

 

После раскрытия скобок все сокращается и остается 0, что и требовалось доказать

(16.1k баллов)